Contribution of Marketing to Commercial Management in an Urban Center from a Sustainable Development Approach - Pancorbo Sandoval, José (2013)
The present investigation has as purpose develop a procedure that allow optimize the localization of new commercial services or reorder those existent looking for to satisfy the commercial expectations of the client in the medium range cities as well as to impact in the decrease of the volumes of urban mobility. For the elaboration of the procedure the author carries out, previous study, the coalition of concepts, technical and tools of the Strategic Urban Planning and City Marketing as well as the most current tools of management of commercial areas.